Histamine - Binding proteins in tick saliva - Paesen, G; Adams, P; Harlos, K; Stuart, D; Nuttall, P (1998)
Ticks, like other haematophagous ectoparasites, secrete in their saliva bioactive substances that counter the host animal's defence reactions at the feeding site and thus facilitate the acquisition of the bloodmeal. We discovered a family of histamine-binding proteins (HBPs) in the saliva of the brown ear tick, Rhipicephalus appendiculatus. HBPs most probably act by mopping up free histamine at the wound site, making it unavailable to the host's H1- and H2-histamine receptors, thus suppressing inflammation. The tick proteins show no sequence homology with known histamine receptors, nor do histamine receptor agonists or antagonists effectively compete with histamine for the binding sites on the tick proteins. The HBPs were expressed in a baculovirus-insect cell expression system. Binding-assays with 3H-histamine reveal high affinities for two of the proteins, but a weaker binding for a third HBP. The high-affinity binders very efficiently suppress histamine-induced contraction of guinea pig ileum. One of the HBPs was crystallized in the presence of histamine, and its structure determined at a 1.2 angstrom resolution. The protein appears to be a member of the lipocalin family, and contains both a high and low affinity histamine-binding site.